Transition-metal-free hydroamination/defluorination/cyclization of perfluoroalkyl alkynes with amidines. Issue 1 (22nd November 2021) - Sun, Li-Wen; Yu, Zi-Lun; Luo, Xin-Long; Ma, Mengtao; Shen, Zhi-Liang; Chu, Xue-Qiang
Abstract : An efficient defluorinative cyclization strategy for the construction of perfluoroalkyl-substituted pyrimidines by using perfluoroalkyl alkynes and amidines as substrates was developed. Abstract : An efficient defluorinative net-[3 + 3]-cyclization strategy for the construction of perfluoroalkyl-substituted pyrimidine derivatives by using a series of perfluoroalkyl alkynes and amidines as starting materials was developed. The present reaction proceeded successfully under transition-metal-free conditions to form two new C–N bonds and a new heterocyclic ring through a sequence of hydroamination, defluorination, and annulation. The desired pyrimidines could be obtained with good functional group tolerance and moderate to good yields. Moreover, the distinctive fluorine effects of perfluoroalkyl substituents are vital for tuning the reactivity of alkynes for the anticipated defluorinative annulation. The pendant π system would lower associated bond dissociation energy significantly compared to that of a nonactivated C(sp 3 )–F bond.